Utilization of Recycled Paper Processing Residues and Clay of Different Sources for the Production of Porous Anorthite Ceramics - Sütçü, Mücahit; Akkurt, Sedat; Akkurt, Sedat (Elsevier Ltd., 2010)
Production of porous anorthite ceramics from mixtures of paper processing residues and three different clays are investigated. Suitability of three different clays such as enriched clay, commercial clay and fireclay for manufacturing of anorthite based lightweight refractory bricks was studied. Porous character to the ceramic was provided by addition of paper processing residues (PPR). Samples with 30-40wt% PPR fired at 1200-1400°C contained anorthite (CaO·Al2O3·2SiO2) as major phase and some minor secondary phases such as mullite (3Al2O3·2SiO2) or gehlenite (2CaO·Al2O3·SiO2), depending on the calcite to clay ratio. Anorthite formation for all clay types was quite successful in samples with 30-40wt% of paper residues fired at 1300°C. A higher firing temperature of 1400°C was needed for the fireclay added samples to produce a well sintered product with large pores. Gehlenite phase occurred mostly at lower temperatures and in samples containing higher amount of calcium (50wt% PPR). Compressive strength of compacted and fired pellets consisting of mainly anorthite ranged from 8 to 43MPa. © 2010 Elsevier Ltd.
Keywords: Clays; Refractories; Anorthite ceramics; Firing; Paper processing residues; Porosity